EFEK TIPE KECURANGAN DAN ANONIMITAS TERHADAP KEPUTUSAN INVESTIGASI AUDITOR INTERNAL ATAS TUDUHAN WHISTLEBLOWING - Darjoko, Felix Joni; Nahartyo, Ertambang (UI Scholars Hub, 2017)
A number of factors affects the effectiveness of whistleblowing system, such as the whistleblower, the wrongdoer, and other relevant parties. However, whistleblowing literature, so far, seems to attend more on whistleblowers’ perspectives. Little is known about aspects from recipient perspectives, especially the effect of psychological biases that can seriously damage the effectiveness of the system. This study extend the whistleblowing literature by experimentally investigating how the fraud type and anonymity influence the recipient decision making process. The results show that internal auditor (as recipient) has lower probability to respond to fraudulent earning management allegation than to that of asset misappropriation. In regard to the anonymity effect, this research is consistent with prior studies in that anonymity provides less credible information for fraud allegation. This study contributes to the literature by highlighting the importance of type of fraud as contextual factor that determine the whistleblowing effectiveness from recipient perspectives.